Factores que influyen en la reincidencia del delito por robo agravado de los adolescentes infractores de la ley del centro juvenil de diagnóstico y rehabilitación trujillo en el período 2012-2013 - Valderrama Fernández, María Ynés (2013)
This research study was performed at the Youth Center for Diagnosis and Rehabilitation Trujillo, which has aimed to describe the personal factors that influence family and recidivism for aggravated robbery of young offenders, also been possible to understand through their life stories, situations, events, events that came personally and your family to graduate from rehabilitative measure which the study goes beyond quantitative data, qualitative research still a net, for it used various methods, techniques and tools that helped in the collection and processing of the information obtained. Similarly to the results obtained indicated that recidivists adolescents in conflict with the law continue in infringing activities because of the possibility of available money, which for them, is a quick and easy option also economic independence for what young people address and resolve their personal expenses according to their need and interest, the influence of his circle of friends is also another indicator to continue in wrongdoing, the presence of frequent arguments and physical aggression, non-standard setting, the absence paternal affection and family communication are elements that lead to teen back repeatedly breaking the law. In conclusion, having a thorough understanding of the situation which is experienced by these young people who can intervene the multidisciplinary team, together with strategic alliances that help achieve the comprehensive rehabilitation and social reintegration of the young offender, because if this does not happen by 70% the teenager again recidivist offenses of aggravated robbery.